STUDY ON FRUIT QUALITY OF SELECTED SEEDED PUMMELO CULTIVARS AND ITS RELATIONSHIP WITH ANTIOXIDANT ACTIVITY CONTENT DURING STORAGE PERIOD - Wahyu Fikrinda; Slamet Susanto; Darda Efendi; Maya Melati (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2015)
Indonesia has number of accessions and cultivars of pummelo which are prospective to be developed. Pummelo contains higher antioxidants thus beneficial for health. This research aimed to get information of physical and chemical quality differences, antioxidant capacity, and explain the relationship between fruit quality and antioxidant capacity of selected seeded pummelo cultivars. Fruit was harvested in Banyuwangi and Magetan while fruit quality assesment was conducted in Laboratory of Agronomy and Horticulture Depart-ment, IPB. The results showed that physical qualities of fruit (weight loss, peel softness and peel color) and chemical qualities (total soluble solids and total titratable acidity) were changed during storage. Adas Nambangan and Banyu-wangi cultivars have better physical and chemi-cal qualities than other cultivars during storage until 10 weeks after harvest because of good visual appearance, the lowest decreased in weight loss and the good ratio of TSS:TTA. Seeded pummelo cultivars with dark red to reddish white fruit pulp had significant higher total phenolic, carotenoid, anthocyanin and anti-oxidant capacity than white fruit pulp. There were negative correlations between antioxidant capacity with colored pulp and total phenolic content. Banyuwangi had the highest antioxidant capacity in the pulp, followed by Bali Merah, Adas Nambangan, Pamelo Magetan, Srinyonya, Bali Putih cultivars.